An Experimental Study with Model Calibration for the Permanent Strain of Granite Residual Soil Subgrade under Drying-Wetting Cycles - Xuefei Yang; Dongxia Chen; Yue Liu; Sheng Zhang (Geofluids)
The permanent strain is one of the most important dynamic properties of the granite residual soil. To systematically study the dynamic deformation characteristics of granite residual soil (GRS) under the drying-wetting (D-W) cycles, a series of dynamic triaxial tests is carried out to obtain the stress-strain relationship of GRS with various fine particle contents subjected to D-W cycles. The experimental results show that the growth of permanent strain consists of two stages, namely, compaction stage and compression stage. The main effect of D-W cycles is reflected in the compression stage. On the other hand, the influence of fine particle contents on the permanent strain occurs mainly at the compaction stage, which can be classified as the lubrication, densification, and asphyxiation, respectively. Subsequently, a new criterion to characterize the permanent strain of GRS is deduced from the experimental results, which accounts for both strains and rates of strains. This criterion illustrates that with the increase of D-W cycles number, the permanent strain evaluation pattern of GRS is gradually changing from plastic stabilization to plastic creep. Finally, a quadratic function model referring to the log-log scale is proposed to fit well the relationship between the permanent strain and loading cycle number of GRS under D-W cycles. It is found that the parameters of the proposed model can physically represent the strain rate, the compression strain, and the compaction strain.